The Relationship of Anemia in Pregnant Women and the Incidence of Premature Delivery: Systematic Review - Arini Banowati Azalia Adnin; Desak Made Sintha Kurnia Dewi (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Anemia causes serious complications for the mother in pregnancy, childbirth and the postpartum period and can result in the birth of a premature baby. Pregnant women with anemia are known to be more at risk of having preterm labor. In Indonesia in 2018 the prevalence of anemia in pregnant women increased to 48.9% compared to 2013 with a prevalence of 37.1%. This study aims to determine the relationship between anemia in pregnant women and the incidence of preterm labor in Indonesia.Subjects and Method: This study uses a systematic review conducted by searching for articles from several databases, namely Neliti and Garuda with a search range from 2017-2020. Article search is based on PICO. P= Pregnant women. I= Supplementation to prevent anemia. C= anemia status. O= The incidence of premature birth. The keywords used to search for articles were “anemia” OR “pregnant women” AND “preterm birth” OR “preterm”. The articles included in this study are full-text articles with a randomized controlled trial study design. Articles were collected using the PRISMA flow chart.Results: There are 6 articles included in this review. The results showed that there was a relationship between anemic pregnant women and premature birth, and the risk was 79.286 times greater for preterm delivery. Effective interventions that can be given in preventing the birth of premature babies in pregnant women are Antenatal Care (ANC) visits, taking 60 mg Fe tablets/day during pregnancy and maintaining diet as well as nutritional intake.Conclusion: There is a relationship between anemic pregnant women and premature birth.Keywords: anemia, premature birth, pregnant women.Correspondence:Arini Banowati Azalia Adnin. Universitas Airlangga. Kemang Pratama 3 Jalan Lantana 1 Blok D1 No12, Bekasi. Email: arini.banowati.azalia2018@fkm.unair.ac.id. Mobile +6287877307124.Journal of Health Promotion and Behavior, (2022), 07(01): 67-76DOI: https://doi.org/10.26911/thejhpb.2021.07.01.07